2008
DOI: 10.1021/jp075143n
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalysis of the Oxygen Reduction Reaction at Adsorbate-Covered Silver

Abstract: The oxygen reduction reaction, the slow kinetics of which is well-known to limit efficient energy production from fuel cells, is shown to be catalyzed at adsorbate-covered silver electrodes when the electrode is irradiated with wavelengths in the visible and near-ultraviolet. We report the photocurrent dependence on adsorbate molecule, electrode voltage, excitation wavelength, and oxygen content of the solution. Comparison of the photocurrent excitation profile with the modulated electroreflectance spectrum id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
4
15
0
Order By: Relevance
“…48 The photocatalytic process of the AgNPs@PDA composites for the degradation of NR can be proposed as follows: The electron in the conduction and valence bands from plasmon-induced AgNPs could reduce oxygen to superoxide radicals, a similar phenomenon is observed on the AgI covered Ag electrode. 49 The generated superoxide radicals migrated from inner AgNPs to the PDA shells outside. The PDA shell, because of its special structures and property, can improve the catalyst.…”
Section: Photocatalytic Degradation Studiesmentioning
confidence: 99%
“…48 The photocatalytic process of the AgNPs@PDA composites for the degradation of NR can be proposed as follows: The electron in the conduction and valence bands from plasmon-induced AgNPs could reduce oxygen to superoxide radicals, a similar phenomenon is observed on the AgI covered Ag electrode. 49 The generated superoxide radicals migrated from inner AgNPs to the PDA shells outside. The PDA shell, because of its special structures and property, can improve the catalyst.…”
Section: Photocatalytic Degradation Studiesmentioning
confidence: 99%
“…Since AgNP exhibited strong absorption close to the photocurrent shoulder with maximum around 420 nm, plasmon-excitation of AgNPs could also participate in the reduction of oxygen. Such phenomena have been observed in roughed Ag substrates under surface plasmon excitation[25]. Further studies are necessary to address this issue.We also investigated the effect of the surface status ofAgNPs on photocurrent generation by two experiments.…”
mentioning
confidence: 84%
“…In addition to the three major elds of applications, plasmonenhanced chemical reactions have also been demonstrated in a wide range of reactions including photoreduction of nitroaromatic compounds, elemental sulphur, O 2 , CO 2 , ferricyanide, and graphene oxide, as well as the mineralization of alcohol and organic acids. 113,[176][177][178][179][180][181][182][183][184] Hung et al showed plasmonic enhancement in CO oxidation reaction using a Au nanoparticle/Fe 2 O 3 composite as a catalyst in a microreactor. 83 The laser excitation of the LSPR of the Au nanoparticles strongly enhanced the CO oxidation rate in the presence of the composite catalyst, as evidenced by the quadrupole mass spectrometer (QMS) signal of CO 2 (Fig.…”
Section: Other Reactionsmentioning
confidence: 99%